PIPIL DOCUMENTS LEGALITY AS PROOF OF LAND OWNERSHIP RIGHTS OWNERSHIP IN BALI - Ketut Diana Rista Pradnyadana; Putu Edgar Tanaya (Transpublika Publisher, 2022)
Pipil as proof of land ownership is not comparable in strength to a certificate. Pipil is used as proof of ownership of a land based on the Customary Agrarian Law which later became the source of the formation of the National Agrarian Law which was subsequently ratified by the Basic Agrarian Law of 1960 which was reinforced by Law No. 24 of 1997 concerning Land Registration. This study aims to find certainty that there is a legal basis for using pipil as proof of ownership rights, to provide information to the public regarding the importance of registering their land with the BPN and as a material consideration for communities who have not changed their proof of land ownership rights to the National Land Agency (BPN). The method used in this study is a normative method by studying laws and regulations and the results of research and writings from legal circles. The main topic of discussion is the legal basis for using pipil as proof of land ownership and the factors that form the basis for why there are still people who use pipil.